MODERN CLINICAL AND MORPHOLOGICAL ASPECTS OF SUBCLINICAL HYPOTHYROIDISM IN PREGNANCY (European Science Methodical Journal, 2024)
Hypothyroidism is a reduced function of the thyroid gland. Subclinical hypothyroidism is characterized by the absence of symptoms, but at the same time, tests signal an increase in TSH (thyroid-stimulating hormone of the pituitary gland - it is responsible for regulating the secretion of thyroid hormones). Therefore, it is very important to take all the tests prescribed by the doctor on time, because timely and correct treatment can prevent the consequences of hypothyroidism.